2022
DOI: 10.1177/20420188221083530
|View full text |Cite
|
Sign up to set email alerts
|

Role of inflammation in diabetic cardiomyopathy

Abstract: The prevalence of type 2 diabetes (T2D) has reached a pandemic scale. Systemic chronic inflammation dominates the diabetes pathophysiology and has been implicated as a causal factor for the development of vascular complications. Heart failure (HF) is regarded as the most common cardiovascular complication of T2D and the diabetic diagnosis is an independent risk factor for HF development. Key molecular mechanisms pivotal to the development of diabetic cardiomyopathy include the NF-κB pathway and renin–angiotens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 83 publications
0
18
0
Order By: Relevance
“…In 1974, the Framingham Heart Study showed that the risk of heart failure was five times higher in people with type 2 diabetes (T2D) (Kannel et al, 1974). T2D and DCM include markers of inflammation such as TNF⍺, IL-6, IL-8, IL-1β, and C-reactive protein (CRP) (Soinio et al, 2006;Bruno et al, 2009;Dinh et al, 2009;Herder et al, 2011;Ramesh et al, 2022). Another pathway activated in diastolic dysfunction associated with DCM is the renin-angiotensin-aldosterone system (RAAS).…”
Section: Cardiomyopathymentioning
confidence: 99%
“…In 1974, the Framingham Heart Study showed that the risk of heart failure was five times higher in people with type 2 diabetes (T2D) (Kannel et al, 1974). T2D and DCM include markers of inflammation such as TNF⍺, IL-6, IL-8, IL-1β, and C-reactive protein (CRP) (Soinio et al, 2006;Bruno et al, 2009;Dinh et al, 2009;Herder et al, 2011;Ramesh et al, 2022). Another pathway activated in diastolic dysfunction associated with DCM is the renin-angiotensin-aldosterone system (RAAS).…”
Section: Cardiomyopathymentioning
confidence: 99%
“…Following NF-κB activation, deleterious inflammatory processes ensue in the myocardium of patients with DM, including cardiomyocyte hypertrophy, fibrosis, and apoptosis, as well as the impairment of myocardial energetics, calcium management, and contractility [ 59 ]. Several human studies have suggested that an augmented systemic inflammatory burden could be predictive of incident HF in individuals with DM.…”
Section: The Role Of Diabetes Mellitus In Heart Failure Pathophysiologymentioning
confidence: 99%
“…Low-grade inflammation is a pathophysiologic factor in type 2 diabetes (T2D) and may have a significant impact on the development of diabetic complications, such as cardiovascular disease (CVD) [ 106 , 107 , 108 ]. GLP-1 suppresses inflammation and promotes gut mucosal integrity [ 10 , 109 ].…”
Section: Glp-1 and Glp-2 As Regulators Of Intestine Integrity And Inf...mentioning
confidence: 99%